National Food Security Mission (NFSM) and Its Impact on Food Security in Narnaund Tehsil - Pardeep Kumar*, Rajesh Malik, Kulvinder Kaur** (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The National Food Security Mission (NFSM), launched in 2007, aims to enhance agricultural productivity and ensure food security in India. This study evaluates its impact on Narnaund Tehsil, Hisar district, Haryana, focusing on wheat and pulse production, farmer benefits, and challenges in implementation. The findings indicate that wheat yields increased from 3.2 tonnes/ha (2006) to 4.5 tonnes/ha (2022), while rice yields rose from 2.1 tonnes/ha to 3.5 tonnes/ha. Farmers benefited from subsidized seeds, fertilizers, and farm mechanization, leading to a 20-30% increase in incomes. However, issues like water scarcity, limited farmer awareness, and market fluctuations continue to challenge sustainable agricultural growth. To maximize NFSM’s benefits, water-efficient irrigation, improved farmer training, and better market access are recommended. Strengthening sustainable farming practices can further enhance food security and economic stability in Narnaund.